1989
DOI: 10.2165/00007256-198908010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Considerations in Training Young Athletes

Abstract: Healthy children evidence smaller values of cardiorespiratory function than adults, but these are in proportion to the smaller body size. At birth, the distribution of muscle fibres and the activity of enzymes in muscle are different from in adults, but these differences disappear at about age 6. On the other hand, muscle fibre thickness increases from birth to about 18 years of age and this is concurrent with increases in muscular strength. The increase in maximal oxygen consumption (VO2max) that accompanies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 66 publications
1
13
0
4
Order By: Relevance
“…Conflicting data exist regarding the influence of training on the child's vital capacity. Pulmonary diffusion capacity in well-trained children is greater than in untrained youngsters and many workers reported increased maximal oxygen consumption (VOj^^^^) as an outcome of endurance training (Zauner et al, 1989). In the study of Sunnegardh and Bratteby (1987) maximal oxygen uptake was assessed in 101 randomly selected 8-and 13-year-old children.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting data exist regarding the influence of training on the child's vital capacity. Pulmonary diffusion capacity in well-trained children is greater than in untrained youngsters and many workers reported increased maximal oxygen consumption (VOj^^^^) as an outcome of endurance training (Zauner et al, 1989). In the study of Sunnegardh and Bratteby (1987) maximal oxygen uptake was assessed in 101 randomly selected 8-and 13-year-old children.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of training on the child's lung volume are somewhat controversial in young athletes (Zauner et al 1989). Some studies reported an increase in vital capacity (Courteix et al 1997;Ekblom 1969;Engstrom et al 1971) or FVC (Baxter-Jones and Helms 1996), while others reported no change with Fig.…”
Section: Effect Of Training On Pulmonary-function Testmentioning
confidence: 99%
“…28 From a physiologic standpoint, aerobic (VO 2 max) and anaerobic capacity increase with age, youth athletes have a higher metabolic cost of running compared with adults, and they have more difficulty dealing with thermoregulation. 29,30 These are critical to understand when treating athletes who may be subjecting themselves to the intense demands of single specialization beyond the more commonly known overuse syndromes discussed herein.…”
Section: Anatomy and Physiology Of The Pediatric Athletementioning
confidence: 99%